Dahschur, Ägypten - Arnold, Felix (e-Forschungsberichte des DAI, 2017)
The focus of the field work at Dahshur (Egypt) lays on the investigation of the area surrounding the valley temple of the Bent Pyramid. The aim was to investigate the development of the temple precinct and its surrounding area. Excavation work was conducted in six sections located to the north, east and south of the temple enclosure. Among the main results are the discovery of a settlement for priests south of the temple and the identification of various rituals that took place in and around the temple precinct.